How Can We Optimize the Value Assessment and Appraisal of Orphan Drugs for Reimbursement Purposes? A Qualitative Interview Study Across European Countries - Blonda, Alessandra; Denier, Yvonne; Huys, Isabelle; Kawalec, Pawel; Simoens, Steven (Frontiers in Pharmacology, 2022)
Introduction The expansion of orphan drug treatment at increasing prices, together with uncertainties regarding their (cost-)effectiveness raises difficulties for decision-makers to assess these drugs for reimbursement. The present qualitative study aims to gain better insight into current value assessment and appraisal frameworks for orphan drugs, and provides guidance for improvement. Methods 22 European experts from 19 different countries were included in a qualitative survey, followed by in-depth semi-structured interviews. These experts were academics, members of reimbursement agencies or health authorities, or members of regulatory or health/social insurance institutions. Adopting a Grounded Theory approach, transcripts were analysed according to the QUAGOL method, supported by the qualitative data analysis software Nvivo. Results Although participants indicated several good practices (e.g. the involvement of patients and the presence of structure and consistency), several barriers (e.g. the lack of transparency) lead to questions regarding the efficiency of the overall reimbursement process. In addition, the study identified a number of ‘contextual’ determinants (e.g. bias, perverse effects of the orphan drug legislation, and an inadequate consideration of the opportunity cost), which may undermine the legitimacy of orphan drug reimbursement decisions. Conclusion The present study provides guidance for decision-makers to improve the efficiency of orphan drug reimbursement. In particular, decision-makers can generate quick wins by limiting the impact of contextual determinants rather than improving the methods included in the HTA. When implemented into a framework that promotes ‘Accountability for Reasonableness’ (A4R), this allows decision-makers to improve the legitimacy of reimbursement decisions concerning future orphan drugs.